Cyanobacteria as Candidates to Support Mars Colonization: Growth and Biofertilization Potential Using Mars Regolith as a Resource - Macário, Inês P. E.; Veloso, Telma; Frankenbach, Silja; Serôdio, João; Passos, Helena; Sousa, Clara; Gonçalves, Fernando J. M.; Ventura, Sónia P. M.; Pereira, Joana L. (Frontiers in Microbiology, 2022)
Cyanobacteria are pointed out as organisms that can possibly support Mars colonization, contributing to the production of oxygen and other commodities therein. In this general context, the aim of this work was to evaluate the ability of three species of cyanobacteria (Anabaena cylindrica, Nostoc muscorum, and Arthrospira platensis) and a green microalga (Chlorella vulgaris) to grow using only resources existing in Mars i.e. water and Martian regolith (MGS-1), under an Earth-like atmosphere. A Martian regolith extract was produced and used as culture medium to these species. Their growth was assessed during 25 days, using optical density and fluorometric parameters. After this period, the possible contribution of end-of-life cyanobacteria/microalga as biofertilizing agents was also assessed, using the macrophyte Lemna minor as a vegetable model. Among these species, N. muscorum was the one that showed the best growth performance compared to the other species, while A. platensis and C. vulgaris were not able to thrive on Mars regolith extract. Therefore, N. muscorum should be target of future studies not only due to their role in oxygen production but also their possible use as a food source, as many members of the Nostoc genus. Cyanobacteria and microalgae (A. platensis and C. vulgaris) showed good abilities as biofertilizing agents, i.e. they stimulated biomass (i.e. dry weight) production at levels comparable to the plants that grew on standard synthetic medium. The highest yield was reached with A. platensis, while the lowest was achieved using the media with N. muscorum. FTIR-ATR (Fourier transform infrared with attenuated total reflectance) spectroscopy showed that the differences between plants grown on mediums with or without Martian regolith seems to be related mainly with polysaccharides.